PENEGAKAN HUKUM PEMBERIAN HAK RESTITUSI TERHADAP KORBAN TINDAK PIDANA PERDAGANGAN ORANG DALAM PERSEKTIF KEARIFAN LOKAL DI ACEH - Irwandi Irwandi (AL-ILMU, 2023)
Trafficking is a new form of slavery in the modern age. In the context of trafficking crimes, at least in Indonesia there are laws that guarantee respect for humanity and prosecution of all forms of injustice that can be used to take action against crimes that injure humanity, namely Law Number 21 of 2007 concerning the Eradication of Trafficking Crimes People (Law Trafficking).Article 48 paragraph (1) of Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons (Law Trafficking), states "every victim of the crime of trafficking in persons or their heirs has the right to obtain restitution". Furthermore, paragraph (3) states "the restitution is given and stated at the same time in the court decision regarding the criminal case of trafficking in persons. The purpose of this study is to find out and explain about law enforcement granting the right of restitution to victims of the crime of trafficking in persons. The law and customary courts in Aceh have guaranteed legal certainty regarding the granting of restitution rights for victims of Trafficking However, the right to restitution for victims of  from Trafficking cases that exist in the jurisdiction of the Courts in Aceh is not perfect "Getting Restitution". Compared to the losses they have experienced. This can be seen from the decision of the case which has permanent legal force. Legal certainty is not only written in statutory regulations, but also must be applied to concrete events. Something that is contained in the law is an abstract thing. Therefore the abstract becomes certain when it is applied concretely in reality. It is suggested to the authorities to make implementing regulations regarding mechanisms or procedures as well as oversight on how to ensure legal certainty of the restitution rights of Trafficking victims. It is recommended to the authorities to provide legal certainty for victims of Trafficking in accordance with the new Trafficking Law and local wisdom in Aceh so that it contains clear and useful legal certainty regarding the restitution rights of Trafficking victims. Keywords: Right of Restitution, Victims, Trafficking in Persons.